Efficacy of IVIG therapy for patients with sepsis: a systematic review and meta-analysis - Bo Pan; Pan Sun; Renjun Pei; Fangzhao Lin; Haijun Cao (Journal of Translational Medicine, 2023)
Abstract Background Sepsis is an overwhelming reaction to infection that comes with high morbidity and mortality. It requires urgent interventions in order to improve outcomes. Intravenous immunoglobulins (IVIG) are considered as potential therapy in sepsis patients. Results of trials on IVIG as adjunctive therapy for sepsis have been conflicting due to the variability in population characteristics, country geography and drug dosage form in different studies. Methods A systematic article search was performed for eligible studies published up to January, 31, 2023, through the PubMed, Embase, Cochrane Library and Chinese National Knowledge Infrastructure database. The included articles were screened by using rigorous inclusion and exclusion criteria. Subgroup analyses were conducted according to different IVIG types, ages and economic regions. All analyses were conducted using Review Manager 5.4. Quality of studies and risk of bias were evaluated. Results In total, 31 randomized controlled trials were included with a sample size of 6,276 participants. IVIG could reduce the mortality (RR 0.86, 95% CI: 0.77–0.95, p = 0.005), the hospital stay (MD − 4.46, 95% CI: − 6.35 to − 2.57, p = 0.00001), and the APACHE II scores (MD − 1.65, 95% CI: − 2.89 to − 0.63, p = 0.001). Additionally, the results showed that IgM-enriched IVIG was effective in treating sepsis (RR 0.55, 95% CI: 0.40 − 0.76; p = 0.0003), while standard IVIG failed to be effective (RR 0.91, 95% CI: 0.81–1.02, p = 0.10). And the effect of IVIG in reducing neonatal mortality was inconclusive (RR 0.93, 95% CI: 0.81–1.05, p = 0.24), but it played a large role in reducing sepsis mortality in adults (RR 0.70, 95% CI: 0.57–0.86, p = 0.0006). Besides, from the subgroup of different economic regions, it indicated that IVIG was effective for sepsis in high-income (RR 0.89, 95% CI: 0.79–0.99, p = 0.03) and middle-income countries (RR 0.49, 95% CI: 0.28–0.84, p = 0.01), while no benefit was demonstrated in low-income countries (RR 0.56, 95% CI: 0.27–1.14, p = 0.11). Conclusions There is sufficient evidence to support that IVIG reduces sepsis mortality. IgM-enriched IVIG is effective in both adult and neonatal sepsis, while standard IVIG is only effective in adult sepsis. IVIG for sepsis has shown efficacy in high- and middle-income countries, but is still debatable in low-income countries. More RCTs are needed in the future to confirm the true clinical potential of IVIG for sepsis in low-income countries.